Estudo da Teoria do Funcional da Densidade (DFT) na propriedades estruturais e ópticas de nanoclusters de ouro - Rodrigues, Edna da Silva Machado (2019)
Density Functional Theory (DFT) calculations and its time dependent approach (TDDFT) have been performed to investigate the ligand effect on the structural and optical properties of the Au13 and Au13 3+ clusters. In the first part of this work, it has been investigated through the analysis of the potential energy curves, the most favorable coordination site of the NH3, PH3, SCH3 and SeCH3 ligands on the Au13 cluster. The results show that the NH3 and PH3 ligands bind preferentially on top site, while for the other ligands the coordination to the (111) site is energetically more favorable. In addition, it was studied the ligand influence on the structural, electronic and optical properties of the Au13L, where L = NH3, N(CH3)3, PH3, P(CH3)3, SCH3, SCH2Ph, SCH(CH3)NH2, SCH(CH3)Cl, SPh, SPhCH3 , SPhCOOH and SeCH3. The analysis of the electronic stabilities reveals that the Au13SCH(CH3)Cl and Au13NH3 are the most stable among the other clusters of the thiolate or selenolate and of the phosphine or amine-ligated groups, respectively. The ligand effect on the optical absorption spectra of Au13L is relatively small, in which the main change is observed in the intensity of the highest energy peak. In the second part of this work, it has been developed a systematic structural analysis of Au13L8 3+, where L = SCH3, SeCH3, SCH2OCH3 e S(CH3)2NH2, to exam the influence of different ligands. Binding energy calculations indicate that the gold core is more stabilized by the ligand in the following sequence S(CH3)2NH2 > SCH2OCH3 > SeCH3 > SCH3. Natural Bond Analysis (NBO) shows that the strongest electron donation occurs from a lone pair orbital on the sulfur and selenium atoms to the antibonding acceptor o* (Au−S) and o* (Au−Se), respectively. TDDFT calculations have been performed to simulate the optical absorption spectra of Au13L8 3+ in gas phase and under the effect of solvents with different polarities. The absorption spectrum of [Au13(S(CH2)2NH2)8]3+ shows a spectral profile that differs considerably from the others in gas phase and which is strongly affected by solvent.